Images of organization - Morgan, Gareth (Sage Pub. Thousand OaksUS, 1997)
Explores the strengths and limitations of 8 metaphors which have been used to portray a broad range of perspectives on the nature and functioning of organizations. Identifies the metaphors as follows: organizations as - machines; organisms; brains; cultures; political systems; psychic prisons; flux and transformation; and, instruments of domination. Points out that each metaphor provides limited insight, and challenges managers to find appropriate ways of seeing, understanding, and shaping their workplace situations.